IKLIM MIKRO DAN INDEKS KETIDAKNYAMANAN TAMAN KOTA DI KELURAHAN KOMET KOTA BANJARBARU - Nova Annisa; Ahmad Kurnain; Eko Rini Indrayatie; Setia Budi Peran (EnviroScienteae, 2015)
Land conversion is the result of the growth for the urban population. Conversion of green open space (RTH) for development can lead to change in environmental quality. One of the impact to change in environmental quality due to conversion of green space is the increase in local temperature of the city. The existence of RTH have considerable benefits to improve the environmental quality of the city, such as amelioration of microclimate. The aim of this research is to analyze the microclimate and discomfort index of park city for the Komet Village of Banjarbaru City. Microclimate condition as categorized "discomfort expressed by > 50% of the population" to "discomfort expressed by the majority of the population". This condition is affected by the average daily air temperature and the average daily humidity which high at the study site, resulting cause the high of discomfort index  felt by the population especially in the daytime.